2019
DOI: 10.1111/are.14348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary sodium butyrate on growth, diet conversion, body chemical compositions and distal intestinal health in yellow drum ( Nibea albiflora , Richardson)

Abstract: The present study was conducted to investigate the effects of sodium butyrate (SB) on the physical barrier function, pro‐inflammatory response and possible underlying mechanisms in the distal intestine (DI) of yellow drum when fed a high‐SBM diet. Three iso‐proteic and iso‐lipidic diets were formulated with fish meal (FM, the control), 45% fish meal protein replaced by SBM (SBM) and 45% fish meal protein replaced by SBM but supplemented with 0.15% SB (SBM + SB). Fish were fed twice daily for 10 weeks. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 59 publications
6
25
0
Order By: Relevance
“…Based on the results, appropriate supplementation of tributyrin (2 g/kg) significantly increased the growth performance of large yellow croaker. The similar effect was also confirmed by research in turbot ( Scophthalmus maximus ) (Liu et al., 2019), yellow drum ( Nibea albiflora ) (Wu et al., 2019), golden pompano ( Trachinotus ovatus ) (Zhou et al., 2019) and sea bream ( Sparus aurata ) (Robles et al., 2013). This growth promotion effect of tributyrin involved multiple mechanisms.…”
Section: Discussionsupporting
confidence: 59%
“…Based on the results, appropriate supplementation of tributyrin (2 g/kg) significantly increased the growth performance of large yellow croaker. The similar effect was also confirmed by research in turbot ( Scophthalmus maximus ) (Liu et al., 2019), yellow drum ( Nibea albiflora ) (Wu et al., 2019), golden pompano ( Trachinotus ovatus ) (Zhou et al., 2019) and sea bream ( Sparus aurata ) (Robles et al., 2013). This growth promotion effect of tributyrin involved multiple mechanisms.…”
Section: Discussionsupporting
confidence: 59%
“…However, supplementing the grouper diet with NaB reversed the detrimental effects of high-dose 7, resulting in a reduction in the Id/Ph ratio, and signi cantly enhancing intestinal development. Similar results have also been obtained for the yellow drum (Nibea albi ora, Richardson) (Wu, et al, 2020a).…”
Section: Distal Intestinal Damage and Histopathologysupporting
confidence: 84%
“…The syntheses of proteins and lipids are key processes involved in growth response ( Mommsen, 2001 ). In gilthead sea bream and yellow drum ( Nibea albiflora ) (Richardson), the improvement of growth performance may be due to the increase in the availability of essential amino acids of fish fed SB diets ( Robles et al, 2013 ; Wu et al, 2019 ). Wu et al (2019) suggested that supplementation of 0.15% SB increased crude lipid content of the whole body in yellow drum.…”
Section: Introductionmentioning
confidence: 99%